DEFENSE MECHANISM ON THE MAIN CHARACTER OF SHUTTER ISLAND (2010) AS PSYCHOANALYSIS STUDY - Alfina Dewi Fortuna; Endang Yuliani Rahayu (Dinamika Bahasa dan Budaya, 2023)
Abstract The purpose of the research is to examine the ego defense mechanism used by the main character of Shutter Island movie. This thesis uses qualitative approaches to uncover the main character's trauma in Shutter Island Movie, Teddy. This researcher focused on Teddy's defense mechanism, which she used to cope with his trauma. This research uses qualitative approaches to uncover Teddy's trauma and defense mechanism, based on psychoanalysis theories developed by Sigmund Freud, especially related to trauma. Based on the findings, there are three causes of Teddy's trauma. His guilt for killing hundreds of defenseless soldiers during World War II and his regret not taking his wife Dolores to psychiatrists led to her murdering their three children, and Andrew had to kill his wife. His anguish for his family's demise drives him to depression. His id can't stand the pain of remembering the event, so he forms a defense mechanism to avoid the guilt. Those three are associated by four types of ego defense mechanisms: repression, denial, projection, and Displacement. Keywords: trauma, defense mechanism, psycoanalysis,